Novel smart and self-healing cerium phosphate-based corrosion inhibitor for AZ31 magnesium alloy. (1st July 2020) - Calado, Lénia M.; Taryba, Maryna G.; Morozov, Yegor; Carmezim, Maria J.; Montemor, M. Fátima
Graphical abstract: Highlights: Modification of hybrid epoxy-silane coating with Ce(DEHP)3 corrosion inhibitor. Improved corrosion protection of AZ31 with Ce(DEHP)3 . Cyclic corrosion inhibition effect of Ce(DEHP)3 . Self-healing in coating defects in the presence of the inhibitor. pH-activated corrosion inhibitor. Abstract: Tri(bis(2-ethylhexyl)phosphate) (Ce(DEHP)3 ) was used as novel corrosion inhibitor for protection of AZ31 coated with an epoxy-silane hybrid coating. Electrochemical Impedance Spectroscopy (EIS) in 0.05 M NaCl showed that Ce(DEHP)3 -modified coating offered superior corrosion protection compared to a reference coating. Localized electrochemical techniques (Localized Electrochemical Impedance Spectroscopy – LEIS, Scanning Vibrating Electrode Technique – SVET, and Scanning Ion-Selective Electrode Technique – SIET) were employed to assess the corrosion healing effect of Ce(DEHP)3 in defect-containing coatings. Results showed that Ce(DEHP)3 introduces cyclic pH-dependent corrosion inhibition, involving the combined action of cerium and organophosphate ions through formation of protective Ce- and P-containing species.